Synchronization algorithm for remote heterogeneous database environment - Imam, A.A. (Springer Verlag, 2015)
Inconsistencies and lack of uniformity of data and its structure is a deep-seated problem of data synchronization in heterogeneous database environment. In this paper, we proposed a model and a unique algorithm to synchronize data between heterogeneous databases, in order to provide alternative synchronization paths, concurrency in operation and bidirectional mode of data exchange. To achieve this feat, three separate algorithms are generated. In addition, jQuery technology is adopted to determine the active path, and the data is transmitted via web service that operates on XML technology over HTTP protocol. The model is independent of any database vendor or proprietary solutions and can be adapted to any database or platform. While fulfilling the set objectives, our proposed algorithm managed to provide an efficient data exchange mechanism for distributed databases using 3 steps for proper consistency and synchronization along with network utilization when tested with three different databases. Â© Springer International Publishing Switzerland 2015.